Garden Squad : The Plot Thickets - Book 5 - Henry, Julia, 1962- (New York, New York : Kensington Publishing Corp., 2022)
"With springs arrival in Goosebush, Lilly and the Beautification Committee turn their eyes to new projects. A cleanup of the historic Goosebush Cemetery may be in order, after Lilly and Delia find the plots there sorely neglected and inexplicably rearranged. Lilly soon discovers that Whitney Dunne-Bradford snapped up custodianship of the graveyard once she inherited Bradford Funeral Homes. But before Lilly can get to the bottom of the tombstone tampering, she stumbles upon Whitneys body at the Jayne family mausoleum. Though at first it appears Whitney died by suicide, Lilly has doubts, and apparently, so does Chief of Police Bash Haywood, who quickly opens a murder investigation. Plenty of folks in town had bones to pick with Whitney, including her stepdaughter, Sasha, and funeral home employee, Dewey Marsh--all three recently charged with illegal business practices. But when the homicide inquiry suddenly targets an old friend, Lilly and the Garden Squad must rally to exhume the truth before the real killer buries it forever."--Back cover.
"Kensington cozies"--Spine.
Keywords: Retired women -- Fiction; Gardening -- Fiction; Murder -- Investigation; Fiction; Women detectives -- Fiction; Cozy mysteries; Detective and mystery fiction